Juvenile granulosa cell ovarian tumor- a rare presentation - Saha, Eti; Biswas, Sunil Kumar; Saha, Dipanwita (Mediscope, 2015)
Juvenile granulosa cell tumor is a rare gynecologic malignancy. A fourteen year old girl was brought to the emergency with acute abdominal pain with distension of abdomen and admitted in surgical unit, clinically suspected perforation of gut. Transabdominal ultrasonography revealed a right adenexal irregular mass with a moderate amount of ascitic fluid. On laparotomy, it was suspected malignant ovarian tumor stage Ic, and then ipsilateral salphingoophorectomy was done considering the age of the patient. It was juvenile Granulosa cell tumor which confirmed by histo-pathologically. The epidemiology, natural history, presentation, histological and imaging appearances, prognosis and treatment of this malignancy were reviewed. DOI: http://dx.doi.org/10.3329/mediscope.v1i1.21636 Mediscope Vol. 1, No. 1: 2014, Pages 36-39